Artificial intelligence: protection and defence of human rights (ethical aspect) - Yu. M. Zhornokui (Bulletin of Kharkiv National University of Internal Affairs)
Taking into account the ethical foundations of the use of artificial intelligence in the field of human rights, the article warns that artificial intelligence has no morals and customs, since morality is usually personal in nature and there is no justification for its repeatability. As a result, artificial intelligence does not have the status of a separate personality, and by using it, the developer or owner is recognised as a participant in civil turnover. Nevertheless, it is assumed that artificial intelligence may replace humans in the future. Therefore, it is necessary that such a replacement is made fairly and compensation is provided if necessary.